Cell Cycle Checkpoint Control Protocols - Lieberman, Howard B.; Lieberman, Howard B. (Methods in Molecular Biology,, 2004)
In recent years, cell cycle checkpoints, cellular mechanisms that control the cell cycle and ensure genomic stability, have emerged as significant factors in carcinogenesis and in cancer cells. In Cell Cycle Checkpoint Control Protocols, leading investigators present their best methodologies to probe the mechanisms underlying cell cycle regulation and checkpoint control. Using mammalian, yeast, and frog systems, these experts describe readily reproducible methods to induce cell cycle checkpoints, detect changes in cell cycle progression, identify and analyze genes and proteins that regulate the process, and characterize chromosomal status as a function of cell cycle phase and progression. Each fully tested technique includes step-by-step instructions written by an investigator who performs it frequently, an introduction explaining the principle behind the method, equipment and reagent lists, and tips on troubleshooting and avoiding known pitfalls. Taken as a whole, the collection describes the major methodologies used by researchers in the field. Cutting-edge and highly practical, Cell Cycle Checkpoint Control Protocols provides an extensive array of detailed protocols by which both experienced and novice investigators may successfully illuminate questions concerning cell cycle control.